O koncepcji i doświadczeniach z wykładu "Wstęp do analizy funkcjonalnej i wypukłej" dla kierunku Ekonometria i Informatyka w Szkole Głównej Gospodarstwa Wiejskiego w Warszawie - Strasburger, Aleksander (On Concept and Experiences Gained by Conducting Lectures "An Introduction to Functional and Convex Analysis" Addressed to Students of Computer Sciences and Econometrics At the Warsaw Agricultural University, 2006)
In the years 2002/03-2004/05 the author of the article has lectured an introductory course of functional and convex analysis to second year students at the Interfaculties' Studies in Computer Sciences and Econometrics at the Warsaw Agricultural University . The time scope of the lecture was 2+2 lecture hours ((lectures and practical classes). On entering this course students had completed a broadly outlined one-year course of mathematical analysis and a one semester course in linear algebra. The aim of the course could be described as accessible, but nevertheless logically coherent presentation of the main notions and tools used for solving problems related to mathematical foundations of optimization theory and other encountered in mathematical economics and information sciences. The article describes a sketch of the program of such a course, based on experiences gained through the years of lecturing.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1117, s. 172-179